“As crianças do morro branco”: uma etnografia da infância Tentehar-Guajajara - OLIVEIRA, Cynthia Helena Chaves (2022)
I understand that childhood is socially constructed and varies according to the time and space in which children live. When it comes to Tentehar-Guajajara childhood, I realize that there is a void in the social sciences of studies that highlight this phase of life and take into account the point of view of children. Thus, the motto of this research is the childhood conception of the Tentehar-Guajajara people.I seek to analyze how childhood is experienced by tentehar guajajara children in Morro Branco Village in Grajaú (Maranhão), identifying the experience with childhood among these people, verifying their daily experience in the village/community, and analyzing the elements that constitute this childhood in their social organization. To account for this task, I use ethnographic research based on the observation proposed by Malinowski (1976) or geertz's "being there" (2005), since this method has presented itself as the best way to have access to the children's universe. I use techniques that are guided by the anthropological categories of imagination and creativity (SOUSA, 2015), which allow us to understand the other ways of saying the child that are beyond orality, such as participating in their games and being among them. Although children are the main subjects of this research, I understand that the conception of childhood develops in an intergenerational perspective, in which adults also shape the definitions of what it is to be a child and childhood. Therefore, they are also my interlocutors in this work. With adults, I resort to interviews and, especially, informal conversations. To give body to the production of data, I make use of the theoretical framework present in Child Anthropology and Indigenous Ethnology, referring to authors such as: Antonella Tassinari (2007); Clarice Cohn (2000; 2005; 2019); Emilene Sousa (2004; 2012; 2014; 2015; 2018); Camila Codonho (2007); Anete Abramowicz et al. (2010); Viveiros de Castro (1996), Zannoni (1999), among others. Regarding the results, observing their practices and their daily life, I was able to understand what conception the Tentehar-Guajajara people have about childhood and their understanding of being a child, as well as identifying some markers that permeate this childhood. Thus, I identify four elements that are fundamental for these children: a) the rituals, specifically, the Girl-Girl's Feast and the Boy's Feast; b) the belief system; (c) learning; and d) the ludicity.